The Effect of Try-in Paste Shade and Framework Design on the Color Characteristics of Dental Zirconia Restorations - Abolghasem Mohammadi; Seyed Alireza Gerami; Sara Tavakolizadeh; Rahab Ghoveizi; Ehsan Rouhollahpour Ahangar (Journal of Dentistry)
Background: Favorable esthetic and mechanical qualities, together with rapid advancements in CAD/CAM technology, have increased the adoption of zirconia restorations. Despite acceptable optical characteristics of zirconia, achieving natural tooth color resemblance remains challenging.Purpose: This study was conducted to determine how the try-in paste shade, tooth region, and framework design affect the color properties of zirconia restorations.Materials and Method: In this in vitro study, a maxillary central incisor was prepared and scanned. Frameworks with four different designs were fabricated. Ten crowns were designed in each group categorized as simple core (SC), dentin core (DC), trestle design core (TC), and monolithic crown (MC). Veneering was performed for all groups except MC. Subsequently, all crowns were cemented with try-in paste Bisco CHOICE 2 cement in shades A1-A3 and B1. The color data (Lab) were determined using the SpectroShade Micro II device. Color difference (ΔE) with the Lab B2 color sample as the target color was calculated using the CIE ΔE 2000 formula. Data analysis was performed using the repeated measure ANOVA test.Results: Zirconia core design, tooth region and cement shade, significantly impacted the ΔE and there were interactions among these factors. The highest ΔE was observed when no cement was used, while the lowest ΔE was observed with A2 cement. Among the various framework designs, the lowest and highest ΔEs were observed in MC and, SC frames, respectively (p Value < 0.05).Conclusion: In the light of the findings of current study, minimum ΔE can be achieved with trestle design framework at the middle portion of the tooth. The try-in paste shade also has a considerable impact on the final ΔE value.